Beteiligung interkulturell gestalten Ein Lesebuch zu partizipativer Stadtentwicklung - INTERPART, Autor*innen-Kollektiv (De Gruyter, 2022)
How can urban planners and developers design intercultural spaces of participation? What is the role of analog and virtual narrative spaces, digital services, and online participation tools? And how can institutional change in planning departments be initiated? This reader reflects on the experiences of a three-year transdisciplinary research project that explored these questions in real-world laboratories in two German cities. It presents strategic considerations, design principles and tools from the project-encouraging reflection on prerequisites for intercultural dialog such as language, communication, networks, and process design.